THE DISTINCTIVENESS AND INTERRELATEDNESS OF THE PRIVILEGES AND IMMUNITIES OF PARLIAMENT: A COMPARISON OF THE NAMIBIAN AND SOUTH AFRICAN JURISDICTIONS - Mbuzeni Johnson Mathenjwa; Lindelwa Mhlongo (Obiter, 2018)
The terms “privileges” and “immunities” in relation to parliament are used interchangeably in the literature. A comparison of the privileges and immunities of parliament in the Namibian and the South African jurisdictions has shown that these are distinctive but interrelated. Major dissimilarities in Namibian and South African law in this regard are discernible. In the Namibian system, certain weaknesses are identified in the legal framework for the privileges and immunities of parliament. Recommendations are made based on these identified gaps with a view to improving the law relating to the privileges and immunities of parliament.